Mengenal Allah melalui Pewahyuan - Anwar Three Millenium Waruwu (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Revelation is God's effort, which can be seen from the words and what He does to reveal Himself and His will to humans. In that way, He revealed Himself to man, and man could know Him. However, human knowledge of God is minimal because of the lack of human awareness about revelation. This research examines "Bible Revelation" as a revelation that complements human efforts to increase knowledge about God. The study will describe and reveal efforts to know God through the Bible with a qualitative approach. The research results confirm that as the word of God, the Bible is a revelation. That human can access to understand God, know Him, understand His purposes, and understand His will.